2021
DOI: 10.1186/s13195-020-00713-3
|View full text |Cite
|
Sign up to set email alerts
|

Four subgroups based on tau levels in Alzheimer’s disease observed in two independent cohorts

Abstract: Background As Alzheimer’s disease (AD) pathology presents decades before dementia manifests, unbiased biomarker cut-points may more closely reflect presence of pathology than clinically defined cut-points. Currently, unbiased cerebrospinal fluid (CSF) tau cut-points are lacking. Methods We investigated CSF t-tau and p-tau cut-points across the clinical spectrum using Gaussian mixture modelling, in two independent cohorts (Amsterdam Dementia Cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
0
22
2
Order By: Relevance
“…The sustained elevation of YKL40, NCAM-1, and CCL23 may represent an ongoing pathological process in the survivors of COVID-19 as the levels did not decline below those recorded at admission [ 46 , 51 , 107 ]. These bio-spectrum markers are not specific to one type of dementia but rather represent the beginning or acceleration of underlying neurodegeneration processes in the wake of COVID-19 [ 1 , 13 , 108 , 109 ]. This finding is consistent with the suggestion of ongoing brain injury in post-viral syndromes or COVID-19 long-haulers [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sustained elevation of YKL40, NCAM-1, and CCL23 may represent an ongoing pathological process in the survivors of COVID-19 as the levels did not decline below those recorded at admission [ 46 , 51 , 107 ]. These bio-spectrum markers are not specific to one type of dementia but rather represent the beginning or acceleration of underlying neurodegeneration processes in the wake of COVID-19 [ 1 , 13 , 108 , 109 ]. This finding is consistent with the suggestion of ongoing brain injury in post-viral syndromes or COVID-19 long-haulers [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This raises concerns about the ability of survivors to recover fully from the disease if the initial insult deprived a host of some neuroprotective mechanisms [ 1 , 9 , 13 , 14 , 16 ]. An alteration in the spectrum of neurobiomarkers (protective vs. injury vs. degeneration) suggests a loss of autoregulated homeostasis and has been proposed to explain the origin of dementia [ 99 , 108 ]. Longitudinal surveillance, with a focus on determining a composite level of several biomarkers, may potentially identify survivors most vulnerable to the progress of clinically-evident dementia [ 33 , 56 , 70 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the effectiveness and robustness of dynaPhenoM, we performed comprehensive analysis on the case of progression from MCI to AD based with the OneFlorida database as development cohort (including 2,995 patients), and the MarketScan database (including 18,805 patients) and the Mount Sinai database (including 689 patients) as validation cohorts. As seen in existing research (18,(60)(61)(62), AD is highly heterogenous, thus categorizing patients into different clinically coherent subgroups is important for understanding the mechanism of AD and develop stratified medicine. Different from existing works that focus on identifying AD subphenotypes according to specific clinical data (e.g., cognitive assessment score) at AD onset, our study identified progression subphenotypes with a diverse set of clinical events during the progression from MCI to AD.…”
Section: Discussionmentioning
confidence: 99%